Adaptive estimation of the dynamic linear model with fixed effects - Tiemen Woutersen; Marcel Voia (The University of Western Ontario, Department of Economics, 2002)
This paper shows how the dynamic linear model with fixed regressors can be efficiently estimated. This dynamic model can be used to distinguish spurious correlation from state dependence and we show that the integrated likelihood estimator is adaptive for any asymptotics with T increasing where T is the number of observations per individual.
Keywords: C31; C33; C11; C14; 330; Panel data; Efficient Estimation; Bayesian Analysis